1985
DOI: 10.1111/j.1440-1681.1985.tb02654.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Responses to Dietary Sodium Manipulation During Normotensive Human Pregnancy

Abstract: Short-term salt loading and salt restriction in a group of normal pregnant women produced no changes in lying, sitting or standing blood pressures or heart rates. Home blood pressures showed no trend to change over the periods of altered salt intake. Although plasma volume and plasma renin activity changed with altered salt intake, there were no relationships between changes in these parameters and changes in mean arterial pressures (MAP) between the low and high salt diets. Capillary permeability and echocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…The non-significant differences in changes in systolic and diastolic blood pressure over pregnancy between the I-and C-groups were only 1 and 0 mmHg in the sitting position and 2 and 1 mmHg in the left lateral recumbent position, indicating that the low-Na diet had no effect on the course of blood pressure during pregnancy. This is in line with three recent studies in which no effect of salt restriction in pregnancy on blood pressure was found (McEniery et al 1985;Brown et al 1987;Steegers et al 1991). However, in the study of Brown et al (1987) subjects who developed hypertension were excluded and in the study of McEniery et al (1985) compliance was not controlled.…”
Section: Effect Of a Low-sodium Diet During Pregnancy On Blood Pressuresupporting
confidence: 90%
“…The non-significant differences in changes in systolic and diastolic blood pressure over pregnancy between the I-and C-groups were only 1 and 0 mmHg in the sitting position and 2 and 1 mmHg in the left lateral recumbent position, indicating that the low-Na diet had no effect on the course of blood pressure during pregnancy. This is in line with three recent studies in which no effect of salt restriction in pregnancy on blood pressure was found (McEniery et al 1985;Brown et al 1987;Steegers et al 1991). However, in the study of Brown et al (1987) subjects who developed hypertension were excluded and in the study of McEniery et al (1985) compliance was not controlled.…”
Section: Effect Of a Low-sodium Diet During Pregnancy On Blood Pressuresupporting
confidence: 90%
“…This suggested that the decreased sensitivity to vasoconstrictor normally observed in pregnancy is reversed, and this could explain the absence of decreased blood pressure. McEniery et al (25) demonstrated that normotensive 18-wk pregnant women receiving a high-sodium diet (300 mmol sodium per day) for 7-10 days had no blood pressure change compared with pregnant women on a regular diet. The discrepancy with our results and other animal studies (3,26) with those of the women of McEniery study could be explained by the level of sodium loading.…”
Section: Discussionmentioning
confidence: 99%
“…McEniery and colleagues studied the effects of short-term manipulations of dietary sodium on blood pressure in pregnancy. 27 In their small study, 22 normal pregnant women, of whom eight were primigravid, were recruited at approximately 18 weeks gestation and allocated to a randomly selected series of three diets, each for 7-10 days: a low sodium (10 mmol per day), a high sodium (300 mmol per day) and the womens' regular diet with ad libitum sodium intake. These short-term dietary manipulations produced no changes in blood pressure or heart rate.…”
Section: Discussionmentioning
confidence: 99%